4(x+28)-3(-x+28)=0

Simple and best practice solution for 4(x+28)-3(-x+28)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+28)-3(-x+28)=0 equation:


Simplifying
4(x + 28) + -3(-1x + 28) = 0

Reorder the terms:
4(28 + x) + -3(-1x + 28) = 0
(28 * 4 + x * 4) + -3(-1x + 28) = 0
(112 + 4x) + -3(-1x + 28) = 0

Reorder the terms:
112 + 4x + -3(28 + -1x) = 0
112 + 4x + (28 * -3 + -1x * -3) = 0
112 + 4x + (-84 + 3x) = 0

Reorder the terms:
112 + -84 + 4x + 3x = 0

Combine like terms: 112 + -84 = 28
28 + 4x + 3x = 0

Combine like terms: 4x + 3x = 7x
28 + 7x = 0

Solving
28 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 7x = 0 + -28

Combine like terms: 28 + -28 = 0
0 + 7x = 0 + -28
7x = 0 + -28

Combine like terms: 0 + -28 = -28
7x = -28

Divide each side by '7'.
x = -4

Simplifying
x = -4

See similar equations:

| 4Z/7-8=*1 | | 2a^2(3a+6a^5)= | | 2x+1+4x-7+90=180 | | -27-(-24)=x/8 | | .25(x-50)=4+3x | | 5(x+10)+3(-x+8)=-10 | | d-86/=4 | | 3a+(6a^2)= | | x+1=4x-20 | | 5+3x=2(-x+6)-22 | | 16=19-3w | | x=0.0048x^3-0.0054x^2+0.157x+1.91 | | x-10+2x-10=46 | | 4(x-5)=x+13 | | 9x-7=x+33 | | 10=1.4x+0.8y | | x=0.0048x^3-0.0054x^2 | | 7+2u=15 | | 1/2x-1/3=5/2 | | 3x+18=5x+14 | | 3x+2(-2x-4)=-4 | | 30x+40=7x+34 | | 3x-7=x+41 | | 4(3x+2)-x=8x-8 | | 7(g-3)+5g= | | 3=4x^(2/5) | | h-6u+7=-29 | | 6=2k-8k | | E(x)=0.0048x^3-0.0054x^2 | | 7(x-6)=5(x+2) | | 6b^2=42b-72 | | 7(8-9x)=0 |

Equations solver categories